1982
DOI: 10.1029/jb087ib07p05541
|View full text |Cite
|
Sign up to set email alerts
|

Information theory lateral density distribution for Earth inferred from global gravity field

Abstract: Information theory inference, better known as the maximum entropy method, is used to infer the lateral density distribution inside the earth. The approach assumes that the earth consists of indistinguishable Maxwell‐Boltzmann particles populating infinitesimal volume elements and follows the standard methods of statistical mechanics (maximizing the entropy function). The GEM 10B spherical harmonic gravity field coefficients, complete to degree and order 36, are used as constraints on the lateral density distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Hide & Horai 1968). More complex methods have also been applied, minimizing the shear strain energy (Kaula 1963) or using the maximum entropy approach (Rubincam 1982). In all cases, the geophysical meaning of the assumptions leading to the inversion is, to the least, debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Hide & Horai 1968). More complex methods have also been applied, minimizing the shear strain energy (Kaula 1963) or using the maximum entropy approach (Rubincam 1982). In all cases, the geophysical meaning of the assumptions leading to the inversion is, to the least, debatable.…”
Section: Introductionmentioning
confidence: 99%
“…of moments (n + 1)(n + 2)/2 Degree of deficiency n(n − 1)/2 0 1 (monopole) 1 (total mass) 0 1 3 (dipole) 3 (center of mass) 0 2 5 (quadrupole) 6 (inertia tensor) 1 3 7 (octupole) 10 (3rd moment) 3 4 9 15 6 5 1 1 2 1 1 0 6 1 3 2 8 1 5 100 201 5151 4950 the physical condition of minimum shear energy in the mantle, Kaula (1963) determined a unique lateral density distribution for the Earth. Rubincam (1982) achieved the unique solution by employing the mathematical constraint of maximum entropy. Likewise, it can be shown that minimizing the norm-2 variance for the lateral distribution also leads to unique solutions.…”
Section: Degree Nmentioning
confidence: 99%
“…This is the approach generally adopted in the maximum entropy inference. Some recent examples are Rietsch (1977), Gull & Daniell (1978), Rubincam (1979Rubincam ( , 1981 and Berrill & Davis (1980). Since Shannon's entropy is defined relative to the arbitrarily chosen independent variable, the probability distribution generated from the principle will be parameter-dependent.…”
Section: P Y Shen and L Mansinhamentioning
confidence: 99%